2009
DOI: 10.1002/ptr.2910
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2C19 inhibitory activity of common berry constituents

Abstract: The cytochrome P450 enzyme CYP2C19 is involved in the metabolism of many commonly prescribed drugs, including proton pump inhibitors, antiepileptics and antidepressants. CYP2C19 inhibitors from food and food supplements may augment the toxicity of these agents and lead to noncompliance with treatment. The present investigation addresses CYP2C19 inhibition by 18 berry constituents using a chemiluminescent assay. Test compounds displayed inhibitory properties in a concentration-dependent fashion, with IC(50) val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…It is necessary to consider herb-drug interactions in order to use herbs safely (9,10,(35)(36)(37)(38)(39). The present study attempted to determine whether rosehip hot water extract inhibited CYP3A4 activity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is necessary to consider herb-drug interactions in order to use herbs safely (9,10,(35)(36)(37)(38)(39). The present study attempted to determine whether rosehip hot water extract inhibited CYP3A4 activity.…”
Section: Discussionmentioning
confidence: 98%
“…A phenomenon similar to this food-drug interaction can be generated between food and drugs. Indeed, it has previously been demonstrated that beverages and food, such as beer, red wine, black and herbal tea, garlic, spices, mace, nutmeg, fruit and fruit juice, tomato juice, and licorice root inhibited enzyme-mediated drug metabolism (9,10,(35)(36)(37)(38)(39). Although rosehip has been used as a food and as a traditional medicine (16), to the best of our knowledge, there is no evidence of an interaction between rosehip and CYP3A4-metabolizing drugs.…”
Section: Introductionmentioning
confidence: 99%
“…There is a dearth of information on the pharmacokinetics properties of phytochemicals from herbs; especially the human oral bioavailability of these herbal components. Few studies available indicates oral bioavailability for anthocyanin, flavonoids and saponins, with the anthocyanins and flavonoids having short half lives (Wu et al, 2002;Yu et al, 2012) In vitro studies have shown that some phytochemicals namely coumarins, saponins, flavonoids and anthocyanins have inhibitory activities on CYP isoforms (Kim et al, 1997;Kimura et al, 2010;Sand et al, 2010). These compounds which are also present in the calyx of Hibiscus sabdariffa might have been responsible for the observed inhibitory activities of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In vitro screening assays with beverages and foods such as beer, red wine, black and herbal tea, garlic, spices, mace, nutmeg, fruits, and fruit juices have all shown the ability to inhibit enzyme-mediated drug metabolism. [5][6][7][8][9][10] CYP3A4 is the most important drug metabolizing enzyme, in that it metabolizes more than 50% of all clinical drugs.11) It is expressed as the most abundant constituent in the human liver CYP enzyme system 12) and is also expressed at substantial levels in the intestinal epithelial cells to metabolize and limit absorption of orally administered CYP3A4 substrate drugs.13) Grapefruit juice is an extensively studied dietary substance that is shown to irreversibly inhibit enteric CYP3A in a mechanism-based manner. [14][15][16] Mechanism-based inhibition (MBI) of CYP3A4 is characterized by nicotinamide adenine dinucleotide phosphate (NADPH)-, time-, and concentration-dependent enzyme inactivation that occurs when some substrates are converted by CYPs into reactive metabolites.…”
mentioning
confidence: 99%
“…[2][3][4] In vitro screening assays with beverages and foods such as beer, red wine, black and herbal tea, garlic, spices, mace, nutmeg, fruits, and fruit juices have all shown the ability to inhibit enzyme-mediated drug metabolism. [5][6][7][8][9][10] CYP3A4 is the most important drug metabolizing enzyme, in that it metabolizes more than 50% of all clinical drugs.…”
mentioning
confidence: 99%